PENGARUH E-SERVICE QUALITY DAN E-TRUST TERHADAP KEPUTUSAN PEMBELIAN TIKET KERETA API (Studi Pada Pengguna KAI ACCESS di Provinsi Lampung) - Ananda, Riris Kharisma; Efendi, Efendi; Saptiani, Winda (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine the effect of e-service quality and e-trust on the decision to purchase train tickets for KAI Access users in Lampung Province. The target population set in this study is KAI Access users in Lampung Province. Data was collected through questionnaires distributed offline and online, sampling using probability sampling with simple random sampling technique and the number of samples was set at 100 respondents. The resulting data were analyzed using descriptive statistics, simple linear regression analysis and multiple linear regression analysis using the SPSS 20.0 application tool. Based on the results of the simple linear regression test, it shows that the e-service quality variable has a significant effect on purchasing decisions by 33,8%, and the e-trust variable has a significant effect on purchasing decisions by 55,4%. The results of the multiple linear regression test explain that e-service quality dan e-trust together have a significant effect on purchasing decisions by 56,2% and the remaining 43,8% of purchasing decisions are influenced by other variables.